2022
DOI: 10.14814/phy2.15384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high‐intensity interval training to exhaustion on the directional sensitivity of the cerebral pressure‐flow relationship in young endurance‐trained men

Abstract: We previously reported subtle dynamic cerebral autoregulation (dCA) alterations following 6 weeks of high‐intensity interval training (HIIT) to exhaustion using transfer function analysis (TFA) on forced mean arterial pressure (MAP) oscillations in young endurance‐trained men. However, accumulating evidence suggests the cerebrovasculature better buffers cerebral blood flow changes when MAP acutely increases compared to when MAP acutely decreases. Whether HIIT affects the directional sensitivity of the cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…19,58,59 Previous studies have shown that dCA at rest 20 and during repetitive squat-stands [58][59][60] was less efficient at regulating decreases in MAP in comparison with MAP increases, and HIIT may exacerbate this directional sensitivity in healthy adults. 61 It is unknown whether individuals post-stroke have lesser dCA sensitivity to decreasing MAP compared to CON, however, this could potentially explain the differences between groups found immediately following HIIT. However, when forcing blood pressure to decrease using a single sit-to-stand following HIIT, we did not find any differences in the cerebral pressure-flow relationship in individuals post-stroke.…”
Section: Spontaneous Dynamic Cerebral Autoregulationmentioning
confidence: 99%
“…19,58,59 Previous studies have shown that dCA at rest 20 and during repetitive squat-stands [58][59][60] was less efficient at regulating decreases in MAP in comparison with MAP increases, and HIIT may exacerbate this directional sensitivity in healthy adults. 61 It is unknown whether individuals post-stroke have lesser dCA sensitivity to decreasing MAP compared to CON, however, this could potentially explain the differences between groups found immediately following HIIT. However, when forcing blood pressure to decrease using a single sit-to-stand following HIIT, we did not find any differences in the cerebral pressure-flow relationship in individuals post-stroke.…”
Section: Spontaneous Dynamic Cerebral Autoregulationmentioning
confidence: 99%